Birth outcomes for Australian mother-infant pairs who received an influenza vaccine during pregnancy, 2012–2014: The FluMum study. Issue 10 (7th March 2017) - McHugh, Lisa; Andrews, Ross M.; Lambert, Stephen B.; Viney, Kerri A.; Wood, Nicholas; Perrett, Kirsten P.; Marshall, Helen S.; Richmond, Peter; O'Grady, Kerry-Ann F.
Abstract: Introduction: In Australia, influenza vaccination is recommended for all women who will be pregnant during the influenza season. Vaccine safety and effectiveness are key concerns and influencers of uptake for both vaccine providers and families. We assessed the safety of receiving an influenza vaccination during any trimester of pregnancy with respect to preterm births and infant birthweight. Methods: We conducted a nested retrospective cohort study of 'FluMum' participants (2012–2014). Our primary exposure of interest was influenza vaccination during pregnancy. The primary outcomes of interest were infant birthweight and weeks' gestation at birth for live singleton infants. Analyses included comparisons of these birth outcomes by vaccination status and trimester of pregnancy an influenza vaccine was given. We calculated means, proportions, and relative risks and performed multivariable logistic regression for potential confounding factors. Results: In the 7126 mother-infant pairs enrolled in this study, mean maternal age at infant birth was 31.7 years. Influenza vaccine uptake in pregnancy was 34%. Most mothers with a known date of vaccination received a vaccine in the second trimester (51%). Those mothers with a co-morbidity or risk factor were 13% more likely to have influenza vaccine during pregnancy compared to other mothers (RR 1.13, 95% CI 1.04–1.24, p = 0.007). Mean weeks' gestation at birth was 38.7 for the vaccinated and 38.8 for the unvaccinated group (p = 0.051). Infants in the vaccinated group weighed 15 g less in birthweight compared to the unvaccinated infants (95% CI −12.8 to 42.2, p = 0.29). Conclusion: Results arising from this large Australian cohort study are reassuring with respect to two critical safety outcomes; preterm births and low infant birthweights. Studies examining a broader range of birth outcomes following influenza vaccination during pregnancy are required, particularly now that maternal vaccination in pregnancy has expanded to include pertussis as well as influenza.